Analisis Kapasitas Dukung Dan Penurunan Fondasi Tiang Pada Bangunan PA Dataran Hunipopu SBB - Tanamal, Stensya Greselli; Titaley, Henriette Dorothy; Siahay, Margie Civitaria (JURNAL SIMETRIK, 2025)
The foundation of a substructure serves as the desired bearing capacity in a pile, which must be able to provide adequate support for the loads acting upon it. The foundation of the Religious Court building in Seram Bagian Barat Regency experienced discrepancies during the pile-driving process, which deviated from the initial plan. This raises the question of whether the pile foundation, with its bearing capacity, can adequately support the acting loads. The aim of this study is to determine the bearing capacity and settlement of the pile foundation of the Religious Court building in Seram Bagian Barat Regency using the Schertmann and Nottingham method, as well as the Meyerhof method, based on cone penetration test (CPT) data. This research showed that the calculated ultimate bearing capacity of a single pile, derived from the CPT data using the Schertmann and Nottingham method, was 34.3601 kN, while the Meyerhof method yielded a value of 202.58 kN. This indicated that the Schertmann and Nottingham method provided the highest bearing capacity, while the Meyerhof method resulted in the lowest. The calculation of pile foundation settlement for a group of three piles indicated a single settlement of 0.03 m and a group settlement of 0.06 m. Keywords : Bearing Capacity, Settlement Of Pile Foundations